Exploring public relations roles and decision-making processes towards achieving best practices among practitioners of Nigerian institute of public relations - Eyo, Nsini Anselem (2021)
This study explores the roles of accredited Nigerian public relations (PR) practitioners, their decision-making involvement, and standards of practices in relation to internationally accepted best practices. Nigerian Institute of Public Relations (NIPR) is challenged by lack of autonomy and interference in its operation of regulating the profession by the executive arm of government. Thus, the objectives of this study explore specific roles of PR practitioners, consequences of non-performance of expected roles, decision making involvement towards achieving organizational goals, and ascertaining the current standards of the profession in meeting with globally accepted practices. The study was conducted in Uyo Akwa Ibom State, South-South region of the Federal Republic Nigeria. A qualitative research approach was deployed for the study. Data collection emanated from semi-structured interviews, observation, and documents reviews. Interview was conducted with 52 informants across three categories of participants: the Nigerian Institute of Public Relations (NIPR), registered PR practitioners and stakeholders. Based on thematic analysis, data was triangulated to ensure consistency and validation of findings for the study. Findings revealed that PR practitioners in Akwa Ibom State were performing mainly technician functions with no involvement in decision making. Further findings showed low standards of practices particularly the regulatory body (NIPR) ability to enforce code of conduct and ensure acceptable standards of practices in the profession. Non engagement of PR personnel and involvement of PR practitioners in decision making militates against the practicality of excellence in PR. The findings suggest urgent need for policy change to enable NIPR as the governing body that regulates the profession to improve its operation and standards. Consequently, the study recommends greater engagement of PR practitioners in management and decision-making roles as well as de-politicization of NIPR. Hence, autonomy of NIPR ensures standardization of profession in line with internationally accepted best practices of PR.